Evidence for increased expression of the vesicular glutamate transporter, VGLUT1, by a course of antidepressant treatment. - Tordera, R; Pei, Q; Sharp, T (2005)
The therapeutic effect of a course of antidepressant treatment is believed to involve a cascade of neuroadaptive changes in gene expression leading to increased neural plasticity. Because glutamate is linked to mechanisms of neural plasticity, this transmitter may play a role in these changes. This study investigated the effect of antidepressant treatment on expression of the vesicular glutamate transporters, VGLUT1-3 in brain regions of the rat. Repeated treatment with fluoxetine, paroxetine or desipramine increased VGLUT1 mRNA abundance in frontal, orbital, cingulate and parietal cortices, and regions of the hippocampus. Immunoautoradiography analysis showed that repeated antidepressant drug treatment increased VGLUT1 protein expression. Repeated electroconvulsive shock (ECS) also increased VGLUT1 mRNA abundance in regions of the cortex and hippocampus compared to sham controls. The antidepressant drugs and ECS did not alter VGLUT1 mRNA abundance after acute administration, and no change was detected after repeated treatment with the antipsychotic agents, haloperidol and chlorpromazine. In contrast to VGLUT1, the different antidepressant treatments did not commonly increase the expression of VGLUT2 or VGLUT3 mRNA. These data suggest that a course of antidepressant drug or ECS treatment increases expression of VGLUT1, a key gene involved in the regulation of glutamate secretion.